Impaired fibrinolytic capacity and increased fibrin formation associate with myocardial infarction - Leander, Karin; Blombäck, Margareta; Wallén, Håkan; He, Shu (Thrombosis and Haemostasis, 2012)
We assessed whether abnormality of haemostasis measured by a newly developed global method is associated with risk of a first myocardial infarction (MI). The global markers Coagulation activation profile (Cp), Fibrinolysis activation profile (Fp) and sum of fibrin optical density over time (Fibrin OD- sum) were determined in plasma from 800 MI cases and 1,123 controls included in the Stockholm Heart Epidemiology Program. Clot lysis time (CLT) was also determined based on raw data of fibrin OD from the global assay. Odds ratios (OR) of MI with 95% confidence intervals (CI) were calculated using logistic regression. A Fp value <10th percentile value in controls was significantly associated with increased MI risk; OR after multivariate adjustments for conventional cardiovascular risk factors 1.66 (95% CI 1.22–2.27). For an abnormally long CLT (>90th percentile value in controls) the adjusted OR of MI was 2.62 (95% CI 1.87–3.66) and for a high Fibrin OD-sum value (>90th percentile in controls) it was 1.86 (95% CI 1.37–2.53). A high Cp value was not significantly associated with MI. In conclusion, we found that abnormal haemostasis in platelet-poor plasma, reflected either as an attenuated fibrinolytic capacity or the resulting increase of fibrin formation, was associated with increased MI risk.
Keywords: Fibrinolysis; blood coagulation; haemostasis; myocardial infarction; cardiovascular disease